The Influence of Storytelling Techniques on Improving the Ability to Listen and Understand Stories in Children Aged 5-6 Years - Siti Isnaini; Nurazila Sari (STIT Attaqwa, 2025)
This writing aims to analyze the influence of storytelling techniques on improving the ability to listen and understand stories in children aged 5-6 years. The development of language skills in early childhood is greatly influenced by the process of social interaction and appropriate stimulation, one of which is through interactive and interesting storytelling techniques. The writing method used is library research with a qualitative approach, reviewing various scientific literature related to storytelling techniques and the development of children's listening skills. The results of the study show that storytelling techniques involving verbal expression, gestures, intonation, and supporting media such as pictures or dolls, significantly increase focus, understanding, and the ability to listen to children's stories. This finding is in line with Vygotsky's language development theory which emphasizes the importance of social interaction and is in accordance with the principles of education in Islam which value storytelling methods as a means of learning. It is recommended that this storytelling technique be integrated consistently in early childhood learning by teachers and parents in order to support children's language and cognitive development optimally.